2020
DOI: 10.1186/s12864-020-6495-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of wild Siberian musk deer (Moschus moschiferus) provides insights into its genetic features

Abstract: Background: Siberian musk deer, one of the seven species, is distributed in coniferous forests of Asia. Worldwide, the population size of Siberian musk deer is threatened by severe illegal poaching for commercially valuable musk and meat, habitat losses, and forest fire. At present, this species is categorized as Vulnerable on the IUCN Red List. However, the genetic information of Siberian musk deer is largely unexplored. Results: Here, we produced 3.10 Gb draft assembly of wild Siberian musk deer with a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…All musk deer species (Moschus spp.) are assessed to be globally threatened due to poaching and habitat loss [19][20][21], with six being ranked as endangered and one as vulnerable (M. moschiferus) according to The IUCN Red List of Threatened Species v. 2015 [22]. The musk deer is characterized by the musk produced by the musk pod on the abdomen of adult males, and the musk is valuable for use in traditional Chinese medicine and perfumes [23].…”
Section: Introductionmentioning
confidence: 99%
“…All musk deer species (Moschus spp.) are assessed to be globally threatened due to poaching and habitat loss [19][20][21], with six being ranked as endangered and one as vulnerable (M. moschiferus) according to The IUCN Red List of Threatened Species v. 2015 [22]. The musk deer is characterized by the musk produced by the musk pod on the abdomen of adult males, and the musk is valuable for use in traditional Chinese medicine and perfumes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Though often reported (e.g., Fu et al, 2020; Wang et al, 2020; Yi et al, 2020; Ludington & Sanders, 2021; Voelker et al, 2021; Okenmor et al, 2022), genome-wide alignment identity metrics like those produced by MuMmer4 are a broad and imperfect measure of assembly accuracy. Therefore, we endeavored to conduct a more in-depth analysis of accuracy by characterizing pairwise alignments of BUSCO sequences shared between assembly types.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of molecular phylogeny indicated that Bovidae and Moschidae diverged from a common ancestor ( Fan Z. et al, 2018 ; Zhou et al, 2019 ; Yi et al, 2020 ). After comparison with all tissues of cows, we found that the mRNA expression pattern of the musk gland was the closest to that of the prostate.…”
Section: Discussionmentioning
confidence: 99%